Food plants in home gardens of the Middle Magdalena basin of Colombia - Diana Villa; Néstor García (Caldasia)
Home gardens are important reservoirs of agricultural diversity essential to support food security in rural communities. In this paper, we describe the richness and composition of species and varieties of plants used for food in home gardens of the municipality of San Pablo in the Middle Magdalena Basin of Colombia, and discuss its possible relations with a set of socio-economic and structural variables. A survey was conducted in 20 home gardens where semi structured questionnaires were administered to the head of each household, and all plants used as food were recorded. The physical characteristics of the home gardens varied widely. Farmers’ ages varied between 28-90 years and the most frequent level of schooling was primary education. In total, 75 species represented by 162 varieties were found. Plantains (Musa x paradisiaca), mangos (Mangifera indica), guavas (Psidium guajava) and cassavas (Manihot esculenta) were the most diverse and frequent crops across gardens. The mean number of species per home garden was 17.5 (SD = 7.1), ranging from 6 to 33. On average 48% of the species recorded were fruits, followed by spices (17%), roots and tubers (12%) and vegetables (9%). Significant correlations were found between food plant richness and farmers’ ages (rs = 0.461, p = 0.04) and food plant richness and number of family members (rs = -0.487, p = 0.03). Home gardens of San Pablo are important regional agrobiodiversity reservoirs that support families’ nutrition.